MicroRNA-181b-2 and MicroRNA-21-1 Negatively Regulate NF-κB and IRF3-Mediated Innate Immune Responses via Targeting TRIF in Teleost - Sun, Yuena; Zhang, Lei; Hong, Ling; Zheng, Weiwei; Cui, Junxia; Liu, Xuezhu; Xu, Tianjun (Frontiers in Immunology, 2021)
Upon recognition of bacterial or viral components by Toll-like receptors (TLRs), cells could be activated to induce a series of reactions to produce inflammatory cytokines, type I interferon (IFN), and IFN stimulating genes (ISG). MicroRNAs (miRNAs) are an important regulatory molecules that are widely involved in the regulatory networks of mammalian inflammation and immune responses; however, in lower vertebrates, the regulatory network of miRNA-mediated immune responses is poorly understood. Here, we report two miRNAs form Miichthys miiuy, namely, miR-181b-2 and miR-21-1, that play a negative role in host antiviral and antibacterial immunity. We found that miR-181b-2 and miR-21-1 are abundantly expressed in gram-negative bacteria, as well as RNA rhabdovirus infection. Inducible miR-181b-2 and miR-21-1 suppress the production of inflammatory cytokines and type I IFN by targeting TRIF, thereby avoiding excessive inflammation. We futher revealed that miR-181b-2 and miR-21-1 modulate antibacterial and antiviral immunity through the TRIF-mediated NF-κB and IRF3 signaling pathways. The overall results indicate that miR-181b-2 and miR-21-1 act as negative feedback regulators and participate in host antibacterial and antiviral immune responses; this finding could provide information for a deeper understanding of the resistance of lower vertebrates to the invasion of pathogens and to avoidance of excessive immunity.